Vestibular Function and Activities of Daily Living - Aisha Harun MD; Yevgeniy R. Semenov MA; Yuri Agrawal MD (Gerontology and Geriatric Medicine, 2015)
Objective: Vestibular dysfunction increases with age and is associated with mobility difficulties and fall risk in older individuals. We evaluated whether vestibular function influences the ability to perform activities of daily living (ADLs). Method: We analyzed the 1999 to 2004 National Health and Nutrition Examination Survey of adults aged older than 40 years ( N = 5,017). Vestibular function was assessed with the Modified Romberg test. We evaluated the association between vestibular function and difficulty level in performing specific basic and instrumental ADLs, and total number of ADL impairments. Results: Vestibular dysfunction was associated with significantly higher odds of difficulty with nine ADLs, most strongly with difficulty managing finances (odds ratio [ OR ] = 2.64, 95% confidence interval [CI] = [1.18, 5.90]). In addition, vestibular dysfunction was associated with a significantly greater number of ADL impairments (β = .21, 95% CI = [0.09, 0.33]). This effect size was comparable with the influence of heavy smoking (β = .21, 95% CI = [0.06, 0.36]) and hypertension (β = .10, 95% CI = [0.02, 0.18]) on the number of ADL impairments. Conclusion: Vestibular dysfunction significantly influences ADL difficulty, most strongly with a cognitive rather than mobility-based task. These findings underscore the importance of vestibular inputs for both cognitive and physical daily activities.